Consumer Knowledge: Effects on Evaluation Strategies Mediating Consumer Judgments - Sujan, Mita (Journal of Consumer Research, 1985)
This study suggests that category-based evaluative responses supplement the piecemeal-based evaluation processes more often studied in Consumer Research. The alternative modes of processing were found to be contingent upon the match/mismatch of information to category expectations. Compared to piecemeal (mismatch) processing, category-based (match) processing resulted in faster impression formation times, more verbalizations related to the product category, fewer verbalizations related to the product's attributes, and fewer references to subtypes. Expertise exaggerated these effects. T he relevance of understanding consumer infor-mation processing strategies has been well estab-lished (Bettman 1979; Wright 1975). One important question involving processing strategies is whether product attributes are reviewed, evaluated, and com-bined to yield an overall evaluation, or whether some simpler processes mediate final judgments and choices.